There is a Relationship between Resource Expenditures and Reference Transactions in Academic Libraries - Hughes, Annie M. (Evidence Based Library and Information Practice, 2013)
A Review of: Dubnjakovic, A. (2012). Electronic resource expenditure and the decline in reference transaction statistics in academic libraries. Journal of Academic Librarianship, 38(2), 94-100. doi: 10.1016/j.acalib.2012.01.001 Objective – To provide an analysis of the impact of expenditures on electronic resources and gate counts on the increase or decrease in reference transactions. Design – Analysis of results of existing survey data from the National Center for Educational Statistics (NCES) 2006 Academic Library Survey (ALS). Setting – Academic libraries in the United States. Subjects – 3925 academic library respondents. Methods – The author chose to use survey data collected from the 2006 ALS conducted by the NCES. The survey included data on various topics related to academic libraries, but in the case of this study, the author chose to analyze three of the 193 variables included. The three variables: electronic books expenditure, computer hardware and software, and expenditures on bibliographic utilities, were combined into one variable called electronic resource expenditure. Gate counts were also considered as a variable. Electronic resource expenditure was also split as a variable into three groups: low, medium, and high. Multiple regression analysis and general linear modeling, along with tests of reliability, were employed. Main Results – The author determined that low, medium, and high spenders with regard to electronic resources exhibited differences in gate counts, and gate counts have an effect on reference transactions in any given week. Gate counts tend to not have much of an effect on reference transactions for the higher spenders, and higher spenders tend to have a higher number of reference transactions overall. Low spenders have lower gate counts and also a lower amount of reference transactions. Conclusion – The findings from this study show that academic libraries spending more on electronic resources also tend to have an increase with regard to reference transactions. The author also concludes that library spaces are no longer the determining factor with regard to number of reference transactions. Spending more on electronic resources is also important to increase both in-person and electronic reference transactions.